CISG Advisory Council Opinion 20 - CISG Advisory Council (Nordic Journal of Commercial Law, 2021)
The CISG-AC started as a private initiative supported by the Institute of International Commercial Law at Pace University School of Law and the Centre for Commercial Law Studies, Queen Mary, University of London. The International Sales Convention Advisory Council (CISGAC) is in place to support understanding of the United Nations Convention on Contracts for the International Sale of Goods (CISG) and the promotion and assistance in the uniform interpretation of the CISG. At its formative meeting in Paris in June 2001, Prof. Peter Schlechtriem of Freiburg University, Germany, was elected Chair of the CISG-AC for a three-year term. Dr. Loukas A. Mistelis of the Centre for Commercial Law Studies, Queen Mary, University of London, was elected Secretary. The founding members of the CISG-AC were Prof. Emeritus Eric E. Bergsten, Pace University School of Law; Prof. Michael Joachim Bonell, University of Rome La Sapienza; Prof. E. Allan Farnsworth, Columbia University School of Law; Prof. Alejandro M. Garro, Columbia University School of Law; Prof. Sir Roy M. Goode, Oxford, Prof. Sergei N. Lebedev, Maritime Arbitration Commission of the Chamber of Commerce and Industry of the Russian Federation; Prof. Jan Ramberg, University of Stockholm, Faculty of Law; Prof. Peter Schlechtriem, Freiburg University; Prof. Hiroo Sono, Faculty of Law, Hokkaido University; Prof. Claude Witz, Universität des Saarlandes and Strasbourg University. Members of the Council are elected by the Council. At subsequent meetings, the CISGAC elected as additional members Prof. Pilar Perales Viscasillas, Universidad Carlos III, Madrid; Professor Ingeborg Schwenzer, University of Basel; Prof. John Y Gotanda, Villanova University; Prof. Michael G. Bridge, London School of Economics; Prof. Han Shiyuan, Tsinghua University, Prof. Yesim Atamer, Istanbul Bilgi University, Turkey, and Prof. Ulrich Schroeter, University of Mannheim. Prof. Jan Ramberg served for a three-year term as the second Chair of the CISGAC. At its 11th meeting in Wuhan, People’s Republic of China, Prof. Eric E. Bergsten of Pace University School of Law was elected Chair of the CISGAC and Prof. Sieg Eiselen of the Department of Private Law of the University of South Africa was elected Secretary. At its 14th meeting in Belgrade, Serbia, Prof. Ingeborg Schwenzer of the University of Basel was elected Chair of the CISGAC.